PENERAPAN MODEL PEMBELAJARAN PJBL-STEAM MENGGUNAKAN MEDIA VIDEO CAMTASIA UNTUK MENINGKATKAN LITERASI PADA PEMBELAJARAN BAHASA INDONESIA KELAS V SDN 120 BERRU, SOPPENG - Firmansyah Firmansyah (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
This best practice is a report on the author's experience in applying the PjBL-STEAM learning model by using the Camtasia video media to improve learning literacy in Indonesian V grade SDN. 120 Berru. The background of this best practice is that the teacher does not involve the role of student activities, the students' learning outcomes are not optimal, especially in the field of literacy, the teacher does not use learning media, the teacher does not motivate and interact with students to produce products from learning outcomes. This best practice research is focused on improving literacy through PjBL-STEM with classroom action research methods consisting of planning, action, observation, and reflection. An instrument for data collection. includes student activity observation sheets, learning outcomes tests, interviews, and documentation. The results of this best practice report are taken data after 2 cycles of classroom action research. The results of the qualitative analysis show that the average score of activities and student learning outcomes has increased. Learning activities in the first cycle of the average score of Indonesian learning activities are 60% in the fairly good category and in the second cycle, there is an increase in the average score of Indonesian learning activities, which is 84% ​​in the good category. The learning results in the first cycle showed an average score of 63 learning activities in a fairly good category and in the second cycle, there was an increase of 77 in the good category. Based on the results of this study, it was concluded that applying the PjBL-STEAM learning model using video Camtasia media can improve learning literacy.